Socio-Economic and Living Conditions of Internal Migrant Labour Living in Visakhapatnam City, India - Godi Rajendra Varma; Godi Sudhakar (Populasi, 2018)
India has seen a high internal migration rate in recent years and among the internal migrants, there is a substantial proportion of poorer migrants involved in low paid and low earning jobs. The present paper reports few socio-economic characteristics and their living conditions of poor migrant labour living in Visakhapatnam city, India, which is one of the world’s fastest growing cities. Migration is one of the reasons for its growth. Data were collected from a sample of 2000 households (with migration duration of 30 days to 10 years) living in 10 slums. This study reveals that migrants are living in sub-human living conditions and are vulnerable to all sorts of risks. It further reports the poor quality of living conditions and services. The vulnerability is a state of being exposed to or susceptible to neglect, which leads to less control over the resources available in the city. They also encounter several constraints such as lack of political voice and basic facilities, low-paid, insecure and hazardous working conditions and less or no access to health care and education. Hence, the government has to recognize poor migrants as a vulnerable urban section that needs special and targeted interventions to improve their living conditions.